DATE RAPE EXPERIENCES AND HELP-SEEKING BEHAVIOUR AMONG FEMALE UNDERGRADUATE STUDENTS OF UNIVERSITY OF IBADAN, NIGERIA (2012)
Date Rape (DR) which is mainly experienced by young women is a public health concern worldwide and is characterised by physical, psychological and social consequences. In Nigeria, there is dearth of information on DR among Female Undergraduates (FUs) in the Universities. This study was therefore designed to determine the prevalence, context of occurence, help-seeking behaviour and level of knowledge relating to DR among FUs of the University of Ibadan. This cross-sectional survey involved the conduct of eight Focus Group Discussions (FGDs) in all the four FU halls of residence. Thereafter, FGD responses were used to develop a semi-structured questionnaire that was used to interview 610 FUs selected using a four-stage random sampling technique. The FUs were selected proportionately from halls of residence, blocks and rooms. Thereafter, one FU per room was interviewed. The instrument included a 6-point knowledge scale and questions relating to DR experiences, context in which DR occurred and victims’ health seeking behaviour. Knowledge scores of 0- 2, 3- 4 and 5- 6 were rated as poor, fair and good respectively. In-depth Interviews (IDI) were subsequently conducted among eight consenting victims of DR. Data were analyzed using thematic approach, as well as descriptive statistics and logistic regression at p = 0.05. The identified forms of DR that could be experienced by FUs were Forced Vaginal Sex (FVS), Forced Anal Sex (FAS), Forced Oral Sex (FOS) and Forced Insertion of Fingers (FIF) into the private part of a woman. It was disclosed that male chauvinism, indecent dressing and alcohol abuse contributed to DR. Respondents’ mean age was 21.0 ± 2.5 years and their median knowledge score was 2.0 (0 – 6). The prevalence of DR was 11.8% and the forms of DR ever experienced were FVS (80.3%), FAS (10.5%), FOS (15.8%) and FIF (32.9%). Only 8.9% of the FUs experienced DR within the year preceding the study. Majority (73.6%) of the respondents who experienced DR had it when they became undergraduates and 52.1% of the perpetrators were fellow students of the University. Respondents aged over 21.0 years (41.5%) were at higher risk of DR (OR: 2.91, 95%CI: 1.36- 6.25). Respondents who had experienced attempted DR (32.2%) were at lower risk of DR (OR: 0.30, 95%CI: 0.14 - 0.64). Majority (83.3%) experienced DR off-campus and 73.3% occurred in dating partners’ houses. Ninety three percent of victims of DR never sought any medical help and reasons included lack of serious physical injury (53.0%) and fear of being stigmatized (10.6%). Most (91.7%) never sought counselling services and 60.5% of them felt it was not necessary. The IDI revealed that the experienced health consequences of DR included -vagina injuries, vagina bleeding, loss of virginity and depression. Date rape occurred among female undergraduates and mostly in perpetrators’ houses outside the University campus. Despite the health effects experienced, victims did not seek help due to psycho-social challenges. Advocacy and public enlightenment aimed at promoting the reproductive rights of females as well as life-skill-training and social support are needed to address the phenomenon.